The texture of contact : European and Indian settler communities on the frontiers of Iroquoia, 1667-1783 - Preston, David L. (David Lee), 1972- (Iroquoians and their world., 2009)
The Texture of Contact is a landmark study of Iroquois and European communities and coexistence in eastern North America before the American Revolution. David L. Preston details the ways in which European and Iroquois settlers on the frontiers creatively adapted to each other's presence, weaving webs of mutually beneficial social, economic, and religious relationships that sustained the peace for most of the eighteenth century.